Analysis of Burning Processes in Turbulent Mixing Axial and Tangential Flows - R. I. Essmann; Y. P. Yarmolchick (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper demonstrates that in the case of turbulent diffusion flame tongues the burning process of combined multiphase fuel is determined by flow structure and conditions for mixing various types of fuel and distributed oxidizer flows. It has been determined that the ratio of air  supplied for burning through axial and tangential channels governs a shape of the flame tongue, its size and process intensity that allows efficiently to optimize technological parameters.